Pelatihan Ilmu Tajwid menggunakan Metode Sorogan untuk mengembangkan kemampuan membaca Al-qur’an pada masyarakat di Desa Sriamur - Dinda Safira; Abdul Ghofur; Aulia Ayu Rohayah (An-Nizam, 2022)
The science of recitation is the basis for reading the Qur'an that is good and correct because the Qur'an is the holy book in Islam that was revealed by Allah SWT to the Prophet Muhammad SAW, and the Qur'an was revealed as a guide for all mankind. In managing life to obtain happiness in this world and in the hereafter. Therefore, the science of recitation becomes the main education to know how to pronounce the letters contained in the Qur'an. if at the time of reading it is wrong in reciting it can change the meaning of the verse of the al quran. the results of observations in the village of sriamur most of the people have difficulty in memorizing various kinds of tajwid and its application when reading the Al-quran. Therefore, this community service program aims to provide recitation training to develop people in reading the Qur'an. This type of community service is carried out directly to the program subject using the sorogan method. This method is a learning that takes place individually between researchers and the community.